Effectiveness of prestressed NSM CFRP laminates for the flexural strengthening of RC slabs - Hosseini, Mhoammadreza Mostakhdemin (2014)
An experimental program was carried out to investigate the effect of the prestressed Near Surface Mounted (NSM) Carbon Fiber Reinforced Polymer (CFRP) laminates on the behavior of reinforced concrete (RC) slabs. Four RC slabs were tested, a reference slab (without CFRP), and three slabs flexurally strengthened using NSM CFRP laminates with different prestress level of the ultimate tensile strength of the CFRP: 0%, 20% and 40%. The experimental program is described and the main results are presented and analyzed in terms of the structural behavior of the RC slabs, failure modes and performance of the NSM technique with prestressed CFRP laminates. The results show that prestressing CFRP laminates with NSM technique is an effective solution to increase cracking, service, yielding and maximum loads of RC slabs failing in bending. By applying 20% of prestressed NSM CFRP laminates, the service and ultimate loads have increased, respectively, 55% and 136%, when the corresponding values of the reference slab are taken for comparison purposes, while 119% and 152% were the increase when applying 40% of prestressed laminates. A numerical strategy was used to evaluate the load-deflection of the tested RC slabs, and a good agreement between experimental and numerical results was obtained.